EFEK HIPOGLIKEMIK POLISAKARIDA LARUT AIR GEMBILI (Dioscorea esculenta) YANG DIEKSTRAK DENGAN BERBAGAI METODE [Hypoglycaemic Effect of Water Soluble Polysaccharides Extracted from Gembili (Dioscorea esculenta) by Various Methods] - . Harijono; Teti Estiasih; Wenny Bekti Sunarharum; I Komang Suwita (Jurnal Teknologi dan Industri Pangan, 2012)
The hypoglycaemic effect of water soluble polysaccharide (WSP) extracted from gembili tuber was studied in this experiment. Extracts from three different methods, an aqueous (water-WSP), papain assisted (papain-WSP), and tempeh inoculum assisted (tempeh-WSP) extractions, were compared. The effects were evaluated by means in vivo test on hyperglycaemic-induced rats by performing the so called blood glucose response, followed by in situ glucose absorption test and short chain fatty acids (SCFA) analysis. A nested experimental design was employed in the experiment. All the three extracts reduced the blood glucose level. The effect of tempeh-WSP extract was comparable to that of the papain-WSP extract, but was not signicantly different from the water-WSP. However, the water-WSP extract tended to have a weaker effect than that of the other extracts. Similar result was found on the SCFA level. The highest SCFA level was found on the rats treated with tempeh-WSP extracts. It was likely that the hypoglycaemic effect of the tempeh-WSP extract was the best.